Tinjauan Penggunaan Metformin tehadap Defisiensi Vitamin B12 pada Pasien Diabetes Melitus Tipe 2 - Natasya Hayatillah; Iswandi Darwis (Majority, 2020)
Metformin is the most widely used oral hypoglycemia drug in the world. This drug become the first choice for the treatment of type 2 diabetes melitus (DM). However, metformin is known to have the effect of creating a vitamin B12 deficiency in type 2 DM patients who consume it. The existing hypothesis states that metformin interferes with the absorption of vitamin B12 through the mechanism of intestinal bacterial overgrowth, the disruption of the vitamin B12 complex with calcium and cubulin receptors. The effect of metformin is known to increase with increasing doses and the length of time uses. The incidence of worsening peripheral neuropathy and megaloblastic anemia have been reported to be associated with the effects of vitamin B12 deficiency in type 2 DM patients taking metformin. To date, there are no clear guidelines that discuss how to diagnose, manage and prevent vitamin B12 deficiency due to metformin, but some research results can be taken into consideration. Vitamin B12 deficiency should be suspected in type 2 DM patients who have taken metformin ≥3 years, at a dose of >1500 mg, experiencing hematological abnormalities or worsening peripheral neuropathy. Prevention that can be done is to give vitamin B12 with dose of 1000 μg intramuscularly per year. As for treatment, an intramuscular injection of vitamin B12 can be given a dose of 1000 μg per day for seven days, followed by an injection once a week for four weeks.